Combined effect of silica dust exposure and cigarette smoking on total and cause-specific mortality in iron miners: a cohort study - Hanpeng Lai; Yuewei Liu; Min Zhou; Tingming Shi; Yun Zhou; Shaofan Weng; Weihong Chen (BMC, 2018)
Abstract Background Both cigarette smoking and long-term exposure to crystalline silica dust were reported to be associated with increased mortality. However, the combined effect of both factors has not been well evaluated. Methods We investigated a retro-prospective cohort of 7,665 workers from one Chinese iron mine with a median follow-up of 42.8 years. Cumulative silica exposure was estimated for each worker by linking work histories with a job-exposure matrix. Cigarette smoking information was collected through face-to-face questionnaires. Hazard ratios (HRs) for total and cause-specific mortality due to silica exposure and smoking were estimated using Cox proportional hazards models. Results A total of 2,814 deaths occurred during 315,772.9 person-years of follow-up. Significantly elevated mortality from all causes, cardiovascular disease, non-malignant respiratory disease and lung cancer was observed among silica-exposed workers, while elevated mortality from non-malignant respiratory disease and lung cancer was observed among smokers. Combined exposure to silica dust and cigarette smoking elevated the proportion of mortality and accounted for 21.2, 76.0, 35.7 and 81.4% of all causes, non-malignant respiratory disease, cardiovascular disease, and lung cancer, respectively. Significant additive joint effects of silica exposure and cigarette smoking on mortality from lung cancer (HR 1.893, 95% CI 0.628 to 3.441) and pneumoconiosis (6.457, 0.725 to 39.114), together with a significant multiplicative joint effect from all causes (1.002, 1.000 to 1.004) were observed. Conclusions The present findings indicated that silica exposure in combination with cigarette smoking accounted for a fraction of extra deaths in our cohort. Our research showed the urgent need for smoking cessation and silica control among iron miners.